Analysis of the factor affecting debt among customers’ of DMDI Shoppe / Nurul Atiqah Ayeb - Ayeb, Nurul Atiqah (2011)
The purpose of this is to examine the factor that affecting credit card debt level among customers of DMDI Shoppe. There are 60 respondents were volunteered to completed multiple self-report instrument for data collection process. Data then was aggregated and analysed using descriptive and Pearson correlation analysis. Most of the respondent experienced the moderate level of credit card debt. There also significant relationship between consumer attitude and lifestyle toward the level of debt. Whereby, the time conscious does not significant toward the debt level. The study correlates with a discussion of the and suggest for the future